1998
DOI: 10.1002/(sici)1097-0274(199802)33:2<164::aid-ajim8>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic monitoring of malathion-exposed agricultural workers

Abstract: The aerial application of malathion over large urban populations in Southern California during the early 1990s raised concerns about adverse health effects, including the potential to cause genetic damage. Workers in the Mediterranean fruit fly eradication program, which involved application of malathion as ground treatment, were studied to examine micronucleus formation and mutation frequencies assessed by the glycophorin A (GPA) assay. In the 1992 pilot project the mean micronuclei level appeared higher in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Other studies [21] that examined micronuclei formation in workers only exposed to a single type of pesticide are much more conclusive with respect to genotoxic effects of agrochemicals in human genetical material than those which monitor populations exposed to mixtures of pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies [21] that examined micronuclei formation in workers only exposed to a single type of pesticide are much more conclusive with respect to genotoxic effects of agrochemicals in human genetical material than those which monitor populations exposed to mixtures of pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…There has been some disagreement with the conclusions of these studies. In the 1980s, the International Agency for Research on Cancer (IARC) postulated that evidence of the mutagenicity of malathion was limited (IARC, 1987), and that the studies both in vitro and in vivo showing cytogenetic changes in humans and other mammals (Windham et al, 1998) have been inconsistent. Nevertheless, with more recent researches (Blasiak et al), the U.S. Agency for Environmental Protection (EPA, 2000) concluded that there was a suggestive evidence of carcinogenicity, but not enough to rate malathion as a potential human carcinogen, even though some authors have shown what seems to be conclusive research of this carcinogenic effect (Giri et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with other causes, cancer mortality shows an upward trend with increasing mortality rates from 99 to 118 per 100.000 population in the period 1980-1998(Medina & Kaempffer, 2001. Also, Chile´s mortality rate from breast cancer in women has increased from 12.3/100.000 in 1990 to 15.0/ 100.000 in 2010, with some fluctuations in between.…”
Section: Introductionmentioning
confidence: 99%
“…Bolognesi et al (1993a) suggested that micronuclei analysis in peripheral blood lymphocytes could be considered a good biomarker of genotoxic exposure to detect early biological effects in individuals having occupational contact with pesticides. The cytokinesis-block micronucleus technique supplied a robust methodology for monitoring human populations (Fenech & Morley, 1985); the studies in populations exposed to pesticides showed positive results with a correlation between the micronuclei frequencies and the years of exposure (Bolognesi et al, 1993a(Bolognesi et al, ,b, 2002Pasquini et al, 1996;Joksić et al, 1997;Falck et al, 1999;Bhalli et al 2006;Costa et al, 2006); positive results without relation to the exposure time (Márquez et al, 2005;Kehdy et al, 2007;Da Silva et al, 2008); positive but not determining this correlation Vlastos et al, 2004;Ascarrunz et al, 2006;Tope et al, 2006;Bolognesi et al, 2009;Rohr et al, 2010); and negative (Barbosa & Bonin, 1994;Scarpato et al, 1996;TitenkoHolland et al, 1997;Calvert et al, 1998;Venegas et al, 1998;Windham et al, 1998;Holland et al, 2002;Pastor et al, 2002a;Bolognesi et al, 2004;Vlastos et al, 2006). The MN assay has also been performed in exfoliated buccal cells, which constitutes a minimally invasive method for monitoring populations exposed to pesticides.…”
Section: Micronucleusmentioning
confidence: 99%